PELATIHAN PENCATATAN KEUANGAN SEDERHANA BADAN USAHA MILIK DESA SAWOJAJAR KECAMATAN KOTABUMI UTARA - Zakiatun Nufus; Sri Puji Lestari; Yuni Elmita Sari; Ungki Prabowo Putra; Aji Setiya Bakti; Yansen Atik; Nanang Mulyana; Juliansyah (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2025)
The problem faced by BUMDes Sawojajar is that all financial transactions have not been recorded accurately. This causes the cassava stall business to be recorded as experiencing losses, due to inaccurate financial records. The income obtained cannot be known, because the recording and the physical money are not the same. In relation to the above problems, it is necessary to hold a simple financial recording training activity for small businesses. The training activity aims to make it easier for BUMDes to record financial transactions carried out, so that it will make it easier for BUMDes to calculate the income obtained and assets owned. This training activity uses the method The method used is the socialization and discussion method. This activity was carried out at the Sawojajar Village Office, North Kotabumi District, North Lampung Regency, on November 13, 2024. The stages of the training activity for making simple financial records for BUMDes, began with providing material on various transactions that usually occur in cassava stall businesses. Then a question and answer session was held regarding the real obstacles that occurred when recording finances. The simple financial recording training activity for BUMDes received a good response from BUMDes managers and Sawojajar Village officials. The training participants were enthusiastic in participating in the training activities. This can be measured from the activeness of participants when interacting during the activity.